Space-borne monitoring of NOx emissions from cement kilns in South Korea - Kim, Hyun Cheol; Bae, Changhan; Bae, Minah; Kim, Okgil; Kim, Byeong Uk; Yoo, Chul; Park, Jinsoo; Choi, Jinsoo; Lee, Jae bum; Lefer, Barry; Stein, Ariel; Kim, Soontae (Atmosphere, 2020)
Nitrogen oxide (NOx) emissions from the South Korean cement industry are investigated with remote-sensing measurements, surface observations, and in situ aircraft measurements. In the Yeongwol, Danyang, and Jecheon regions of central South Korea, six closely located cement factories produce 31 million tons of cement annually. Their impact on the regional environment has been a public-policy issue, but their pollutants have not been continuously monitored nor have emissions inventories been fully verified. Using a newly developed downscaling technique, remote-sensing analyses show that Ozone Monitoring Instrument (OMI) NO2 column densities over the cement kilns have more than twice the modeled concentrations, indicating that the kilns are one of the most dominant NOx emission point sources in South Korea. Observed NOx emissions are stronger in the spring, suggesting that these sources play an important role in the formation of surface ozone and secondary particulate matter. These emissions also slightly increased in recent years, even while most major South Korean cities posted a declining trend in NOx emissions. Photochemical models (during May to July 2015) demonstrate that emissions from the South Korean cement industry have significant environmental impacts, both on surface ozone (up to approximately 4 ppb) and PM2.5 (up to approximately 2 μg/m3).
Keywords: Aircraft measurement; Emissions inventory; Ozone monitoring instruments; Photochemical models; Regional environments; Remote sensing analysis; Secondary particulate matters; Surface observation; Air quality; Cement industry; Health impact; NOx emission; OMI